China's economic growth: Trajectories and evolving institutions - Jun Zhang (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2008)
This paper investigates the institutional reason underlying the change in the trajectory of economic growth in post-reform China, and argues that the trajectory of growth was much more normal during the period of 1978-89 than in the post-1989 era. In the former period, growth was largely induced by equality-generating institutional change in agriculture and the emergence of non-state industrial sector. In the latter period, growth was triggered by the acceleration of capital investments under authoritarian decentralized hierarchy within self-contained regions. Such a growth trajectory accelerates capital deepening, deteriorating total factor productivity and leads to rising regional imbalance. This paper further argues that the change in the trajectory of growth is the outcome of changes in political and inter-governmental fiscal institutions following the 1989 political crisis.
Keywords: H83; P26; 330; economic growth; political institutions; Wirtschaftswachstum; China